1999
DOI: 10.1103/physrevb.59.6083
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and theoretical study ofLi3Nat high pressure

Abstract: X rays from the Cornell High Energy Synchrotron Source were used to study the crystal structure of Li 3 N over a pressure range of 0 to 35 GPa at ambient temperature. Before loading, both the hexagonal D 6h 4 ( P6 3 /mmc) and the hexagonal D 6h 1 ( P6/mmm) phases were present. At modest pressure, the D 6h 1 structure transforms completely into the D 6h 4 structure. A two-parameter Birch equation was fitted to the data to determine the equation of state ͑EOS͒ of the D 6h 4 structure, which is compared with a th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
6
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 18 publications
6
6
0
Order By: Relevance
“…8͒, which was also observed by Ho et al 14 The calculated band gap increases from ␤ → ␥ is 1.5 to 5.5 eV ͑the GGA underestimate of the gap is well known͒. At 5.5 eV one may expect to see a completely transparent sample but, in fact, we see a strong yellow-orange tint.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…8͒, which was also observed by Ho et al 14 The calculated band gap increases from ␤ → ␥ is 1.5 to 5.5 eV ͑the GGA underestimate of the gap is well known͒. At 5.5 eV one may expect to see a completely transparent sample but, in fact, we see a strong yellow-orange tint.…”
Section: Discussionsupporting
confidence: 86%
“…[5][6][7] Its potential for use as an electrolyte in lithium batteries, 4 a hydrogen storage medium [8][9][10][11] and a component in the synthesis of GaN 12 have prompted several studies including investigations into its behavior at high pressure. 13,14 It has been demonstrated that Li 3 N retains its ionic character up to very high pressure while undergoing a significant structural transition. 13 Inelastic x-ray scattering experiments as well as first-principles calculations reveal that this structural change is accompanied by distinct changes in the electronic bands.…”
Section: Introductionmentioning
confidence: 99%
“…The equation of state EOS of the D 6h 4 phase has been measured up to 35 GPa [11]. The experimental P-V n data points 8 are plotted in the same figure which shows nice agreement with our ab initio calculation.…”
Section: Structural and Elastic Properties Of α-And β-Phasessupporting
confidence: 73%
“…The existence of high-pressure β-and γ-phases was confirmed in experiments and their behaviour at high pressure studied by different workers [9][10][11][12][13]. At ~0.5-0.6 GPa α-Li 3 N was observed to transform into a layered hexagonal structure β-Li 3 N (P6 3 /mmc).…”
Section: Introductionmentioning
confidence: 66%
“…It crystallizes in a hexagonal structure, α-Li 3 N, with a space group P6/mmm at ambient conditions at equilibrium pressure. The existence of high-pressure β-and γ-phases was confirmed in experiments and their behaviour at high pressure studied by different workers [1][2][3][4][5]. At ~0.5-0.6 GPa α-Li 3 N is observed to transform into a second layered hexagonal structure β-Li 3 N (P6 3 /mmc).…”
Section: Introductionmentioning
confidence: 74%